Improving intercultural communication in Chinese football clubs: Reconceptualizing meanings of cultural hybridization, glocalization, and expatriate football players’ cultural transition in China - Chen, Yanying; Nor Eeza Zainal Abidin,; Mohd Salleh Aman, (Journal of International Students, 2025)
The Chinese Football Reform and Development Program aims to increase the international competitiveness of men’s national teams through cultural communication with Western countries. However, difficulties in developing such communication have come to light. This study uses semistructured interviews with 20 participants to explore ways to improve intercultural communication and expatriate football players’ adaptation in China. The findings suggest that Chinese football clubs should provide instruction on Chinese language and culture, organize sports cultural exchange activities and psychological construction programs, and establish service systems for accompanying family members. This work challenges glocalization theory by highlighting the rejection of cultural homogenization and the uniqueness of local sports culture.